Trains of electron micro-bunches in plasma wake-field acceleration - Lecz, Z; Andreev, A; Konoplev, I; Seryi, A; Smith, J (IOP Publishing, 2018)
Plasma-based charged particle accelerators have been intensively investigated in the past three decades due to their capability to open up new horizons in accelerator science and particle physics yielding electric field accelerating gradient more than three orders of magnitudes higher than in conventional devices. At the current stage the most advanced and reliable mechanism for accelerating electrons is based on the propagation of an intense laser pulse or a relativistic electron beam in a low density gaseous target. In this paper we concentrate on the electron beam-driven plasma wake-field acceleration and demonstrate using 3D PiC simulations that a train of electron micro-bunches with ∼10 fs period can be generated behind the driving beam propagating in a density down-ramp. We will discuss the conditions and properties of the micro-bunches generated aiming at understanding and study of multi-bunch mechanism of injection. It is show that the periodicity and duration of micro-bunches can be controlled by adjusting the plasma density gradient and driving beam charge.